Histology and Surface Ultra-Structure of the Gill of A Minor Carp, Labeo bata (Hamilton) - Samajdar, I.; Mandal, D. K. (Journal of Scientific Research, 2017)
The histology and surface ultra-structures of the gill epithelium of Labeo bata has been examined through light and electron microscopy. Gill arches bear double rows of primary lamellae and each primary lamella is provided with two rows of delicate rectangular secondary lamellae on its upper and lower surfaces. Gill arches and filaments are lined by thick stratified epithelium while the epithelium of secondary lamella is made up of thin single layered pavement cells. The thin epithelium is supported and kept apart from each other by the pillar cells. The pavement cells are polygonal with well-defined cell boundary and microridges on its apical surface. The epithelial cells are interspersed by large chloride cells located at the base of secondary lamellae and PAS positive mucous cells. Mucous cells are found abundant at the base and tip of the primary lamellae. Taste buds are found on the concave anterior faces of gill arches. The short and soft gill rakers are covered with stratified epithelium. This finding demonstrated that the fish has well developed respiratory system matching to its active life.